Three essays on education from the perspective of the economics of public setor - Zoghbi, Ana Carolina Pereira (2011)
This work consists of three essays organized into chapters that seek to answer questions at first sight unrelated, but with one common denominator, which is the scarcity of public resources devoted to education, overall, especially in lower education. . The first chapter deals with the scarcity of resources devoted to education in a context of population aging. Two hypotheses were tested for Brazilian municipalities on the relationship between the aging of the population and educational expenditure. The first, already proven in the literature, is that there is an intergenerational conflict for resources and the increase of the share of elderly in the population reduces the educational expenditure. The second, proposed here for the first time, is that there should be reduction of competition for resources if there is a relationship of co-residence between young and old. The results indicated that an increase in the share of elderly reduces the educational expenditure per youth. But the results also illustrate that an increase in the share of elderly co-residing with youth (family arrangement more common in Latin American countries) raises the educational expenditure, which reflects a reduction of competition for resources between generations. The second chapter assesses the allocative efficiency of investments in Higher Education. Using the difference between first-year and last-year students’ scores from Enade aggregated by HEI as a product in the Stochastic Production Function, is possible to contribute with a new element in the literature aimed at estimating the production function of education. The results show that characteristics of institutions are the variables that best explain the performance of students, and that public institutions are more inefficient than the private ones. Finally, the third chapter presents evidence that the allocation of public resources in early childhood education is important for a better future school performance. In this chapter was calculated the effects of early childhood education on literacy scores of children attending the 2nd grade of elementary school. The results using OLS and propensity score matching show that students who started school at the ages to 5, 4, and 3 years had literacy scores between 12.22 and 19.54 points higher than the scores of those who began school at the ages 6 years or late. The results also suggest that the returns in terms of literacy scores diminish in relation to the number of years of early childhood education.